Computer based problem compilation training using wondershare quiz creator for junior high school teachers - Farman, Farman; Sarimuddin, Sarimuddin; Chairuddin, Chairuddin; Hali, Fitriyani (Universitas Muhammadiyah Magelang, 2021)
Learning outcomes assessment integrated with information technology is an investment conditioning an honesty to students and increasing the credibility of the National Examination’s results. On the other hand, there must be a harmony in the assessment of learning outcomes with computer-based tests from an early age on students in school education units. Therefore, teachers are required to have the knowledge and ability to compile computer-based tests, as part of the pedagogical competency standards of teachers. The main objective of this science and technology program is to improve the knowledge and skills of teachers as well as to provide maximum service for students in the evaluation of learning at SMP Negeri 1 Baula. This activity wass in the form of training in the preparation of multiple-choice questions and stuffing using the Wondershare Quiz Creator. The steps for this interactive question preparation training activity consisted of preliminary analysis, preparation, implementation and evaluation of the training. With this training, teachers at SMP Negeri 1 Baula had the basic knowledge and skills in making interactive questions using the wondershare quiz creator. This condition was known through the results of observing activities where participants have been able to make computer-based questions. In addition, using wondershare quiz creator as an evaluation tool in learning is good.